Quando narciso se vê feio: o desejo anticolonial a partir das perspectivas dominantes - Beça, Amanda Xavier (2021)
The megalomaniac delusion of Western provincialism in finding itself capable of identifying a universal human ontology was essential to consolidating the epistemic structure of the modern world prevailing to this day. The scenario engendered and advocated the colonial violence to excessively target, objectify and invent an Other that is inadequate to the Westernidealized models and, therefore, less/non-human. Meanwhile, such provincial individual lives with the comfort of not being confronted by any categorization. This neutral and universal individual is offered safeguards in such a way that he has no need to think about his position in the world. His privilege is the condition of being profoundly ignorant towards the historical processes that uphold world baselines, the Other's and his own. Not having the “need” to know what one might colonize gives him the grant of living a quiet life; but as he agrees to comprehend that no position is neutral and starts seeing himself as one of the singularities composing the world, his comfortable zone becomes a minefield. Such individuals get destabilized as commonly they are unable to deal with their constitutive violence. What are the inner conflicts triggered by the desire for decolonizing the self for individuals affected by the hierarchical colonial regime, not pertaining its violence, but its benefits? I think of the resistance and resilience, enthusiasm and discomfort of establishing an anticolonial relationship with the surroundings when one recognizes himself as part of a dominant position benefited by such regime